Aspects of the biology of Cotesia alius (Muesebeck, 1958) (Hymenoptera: Braconidae: Microgastrinae) on Opsiphanes invirae amplificatus Stichel (Lepidoptera: Nymphalidae) in Rio Grande do Sul, Brazil - Salgado-Neto, Geraldo (Estudos de Biologia, 2013)
The species Cotesia alius (Muesebeck, 1958) (Hymenoptera: Braconidae: Microgastrinae) is a larvae parasitoid of Opsiphanes invirae amplificatus Stichel (1904) (Lepidoptera: Nymphalidae). Hymenopteran parasitoids larvae and pupae are recorded acting as defoliators of palm. Concerning the scientific and economic importance of these interespecific relationship, and aiming to increase the knowledge to natural and conservative biological control, the present study records in the State of Rio Grande do Sul State, Brazil, some data on the biology of this C. alius as larval parasitoid of O. invirae amplificatus Stichel (1904). Based on 35 postures were recorded 4581 cocoons. On 16 postures (48%) observed all cocoons were open and empty, indicating that all parasitoids emerged (Normal). In the 19 remaining postures (52%) (Altered), 134 cocoons (6%) were closed with C. alius intacts in six postures (40%) (Intacts) or remains (fragments) (44%), and in Eulophidae intact within three postures (16%). These data can be used in mass rearing of parasitoids, and biological control of defoliator’s palm.